Localization of germ plasm‐related structures during sea urchin oogenesis. Issue 1 (3rd November 2015) - Yakovlev, Konstantin V.
Abstract : Background: Animal germ cells have specific organelles that are similar to ribonucleoprotein complex, called germ plasm, which is accumulated in eggs. Germ plasm is essential for inherited mechanism of germ line segregation in early embryogenesis. Sea urchins have early germ line segregation in early embryogenesis. Nevertheless, organization of germ plasm‐related organelles and their molecular composition are still unclear. Another issue is whether maternally accumulated germ plasm exists in the sea urchin eggs.Results: I analyzed intracellular localization of germ plasm during oogenesis in sea urchin Strongylocentrotus intermedius by using morphological approach and immunocytochemical detection of Vasa, a germ plasm marker. All ovarian germ cells have germ plasm‐related organelles in the form of germ granules, Balbiani bodies, and perinuclear nuage found previously in germ cells in other animals. Maternal germ plasm is accumulated in late oogenesis at the cell periphery. Cytoskeletal drug treatment showed an association of Vasa‐positive granules with actin filaments in the egg cortex.Conclusions: All female germ cells of sea urchins have germ plasm‐related organelles. Eggs have a maternally accumulated germ plasm associated with cortical cytoskeleton. These findings correlate with early segregation of germ line in sea urchins. Developmental Dynamics 245:56–66, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Female germ cells of sea urchins have electron‐dense nuage material that resemble germ plasm‐related organelles. In early previtellogenic oocytes, Balbiani bodies were detected Vasa distribution coincide with position of germ plasm‐related organelles. In eggs, cortical actin filaments are essential for cortical localization of germ plasm.